IMPLEMENTATION OF SIMPLE ADDITIVE WEIGHTING METHOD IN THE DETERMINATION SYSTEM OF THESIS SUPERVISOR - Renny Puspita Sari; Ferdy Febriyanto; Ibnur Rusi (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2021)
Majors are part of higher education institutions that a very important role determining the thesis student supervisor . At the Department of Information Systems, Faculty of Mathematics and Natural Sciences (MIPA) the determination of the thesis supervisor is carried out through a lecturer meeting based on its title in accordance with the competence of the lecturer who will guide, regardless of the number of lecturers' workload or the number of students being supervised. The results of the decision of the meeting to determine the supervisors will be announced to students after the meeting is held. This flow inefficient and may lead to ineffective determination of the supervisor . The final result of the system shows that the Simple Additive Weighting (SAW) method can be applied to determine the weight value of each attribute so as to produce a ranking of each alternative lecture who will be selected as a student supervisor for the thesis according to the result of computerized and accurate calculations.